If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + (-7x + -30) = 36 Reorder the terms: -7x + (-30 + -7x) = 36 Remove parenthesis around (-30 + -7x) -7x + -30 + -7x = 36 Reorder the terms: -30 + -7x + -7x = 36 Combine like terms: -7x + -7x = -14x -30 + -14x = 36 Solving -30 + -14x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + -14x = 36 + 30 Combine like terms: -30 + 30 = 0 0 + -14x = 36 + 30 -14x = 36 + 30 Combine like terms: 36 + 30 = 66 -14x = 66 Divide each side by '-14'. x = -4.714285714 Simplifying x = -4.714285714
| 9mn/4n | | -2x^2+6x+8=12 | | -1=-5-4s | | 18z^3+9z^2-50z-25=0 | | x^2=y^2-20.25 | | 4(-5x+35)-x+7=0 | | 5x/2-8=2x-7/6 | | 2s+7=-5s | | 10a-83=203 | | X=(18+8) | | x=(x)(x) | | 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 | | 9x+-9+9x= | | f(x-3)=5x^2-x-8 |